Implicações teórico-metodológicas para a implementação do Programa de Alimentação Escolar Sustentável em Marechal Cândido Rondon, Paraná - Garcia , Jaciara Reis Nogueira (2021)
Public policies that guarantee human rights and present a broad vision of all should focus on seeking to strengthen sustainable agrifood systems. Thus, as the National School Feeding Program (PNAE), is the oldest and most comprehensive public policy in the area of food and nutrition in the country, to achieve its goal of providing school meals and actions of food and nutrition education to students enrolled in all public schools. This should also be a health promoter of sustainable development and Food and Nutritional Security, with actions that involve the fight against social inequalities and promote a dignified life for all. Objective: To identify and understand the theoretical and methodological contributions of the implementation of the Sustainable School Feeding Program in the municipality, and from the experience demonstrate how the implementation of the Public-School Feeding Policy can stimulate and support local sustainable development, Food and Nutritional Security and the health of individuals. Methodology: A qualitative- quantitative exploratory case study was carried out, structured in four articles. The survey and document analysis were carried out, as well as the systematization of data from the Program in the municipality, based on official and scientifically based documents. The graphic representation and analysis of the network was performed using the Ucinet and NetDraw software, and the graphic demonstration of the implementation processes using the BPMN notation by means of the Bizagi Modeler software. Through narrative research the implementation of the Program in the municipality was presented by the nutritionist and the perception of other actors (municipal managers, directors, cooks, and farmers) who participated in a semi- structured interview. Results: Dimensions and variables were proposed for the analysis of the program based on the promotion of sustainable development, a sociometric analysis of the network of social actors involved in the municipal program was performed, critical points and challenges were pointed out in all the stages necessary for the implementation of the Sustainable PNAE, both because of difficulties due to normative guidelines and management failures, and the results of the purchase of food from family farming during the period of suspension of classes caused by the Covid-19 pandemic were demonstrated. It was concluded by this work that the implementation of Sustainable PNAE is given by political-organizational and technical-operational aspects that depend on the political will and performance of managers, that the nutritionist responsible for the program occupies a prominent place as enforcer of the rules and articulator of various interdisciplinary actions and the formation and cooperation in a network of internal and external actors involved in the search for sustainable development, thus highlighting the need to structure a more effective control and inspection system of PNAE, in addition to creating tools and indicators to evaluate the achievement of the Program's objectives that can provoke changes according to the specificities of Brazilian municipalities.